AWEU-Net: An Attention-Aware Weight Excitation U-Net for Lung Nodule Segmentation - Syeda Furruka Banu (MDPI AG, 2021)
Lung cancer is a deadly cancer that causes millions of deaths every year around the world. Accurate lung nodule detection and segmentation in computed tomography (CT) images is a vital step for diagnosing lung cancer early. Most existing systems face several challenges, such as the heterogeneity in CT images and variation in nodule size, shape, and location, which limit their accuracy. In an attempt to handle these challenges, this article proposes a fully automated deep learning framework that consists of lung nodule detection and segmentation models. Our proposed system comprises two cascaded stages: (1) nodule detection based on fine-tuned Faster R-CNN to localize the nodules in CT images, and (2) nodule segmentation based on the U-Net architecture with two effective blocks, namely position attention-aware weight excitation (PAWE) and channel attention-aware weight excitation (CAWE), to enhance the ability to discriminate between nodule and non-nodule feature representations. The experimental results demonstrate that the proposed system yields a Dice score of <semantics>89.79%</semantics> and <semantics>90.35%</semantics>, and an intersection over union (IoU) of <semantics>82.34%</semantics> and <semantics>83.21%</semantics> on the publicly available LUNA16 and LIDC-IDRI datasets, respectively.